Solve the equation. \[ 2=\frac{7}{2 x-1}+\frac{-3}{(2 x-1)^{2}} \]
Solución de tutoría real
Responder
Solución
Revisado y aprobado por el equipo de tutoría de UpStudy
Beyond the Answer
To solve the equation \[ 2 = \frac{7}{2x - 1} + \frac{-3}{(2x - 1)^2}, \] we first eliminate the fractions by multiplying both sides by \((2x - 1)^2\): \[ 2(2x - 1)^2 = 7(2x - 1) - 3. \] Expanding both sides: \[ 2(4x^2 - 4x + 1) = 14x - 7 - 3. \] \[ 8x^2 - 8x + 2 = 14x - 10. \] Next, we move all terms to one side of the equation: \[ 8x^2 - 8x + 2 - 14x + 10 = 0, \] which simplifies to \[ 8x^2 - 22x + 12 = 0. \] Now, we can divide the entire equation by 2: \[ 4x^2 - 11x + 6 = 0. \] Next, we will use the quadratic formula \( x = \frac{-b \pm \sqrt{b^2 - 4ac}}{2a} \), where \( a = 4, b = -11, c = 6 \): Calculating the discriminant: \[ b^2 - 4ac = (-11)^2 - 4(4)(6) = 121 - 96 = 25. \] Now substituting it into the formula gives: \[ x = \frac{11 \pm \sqrt{25}}{8} = \frac{11 \pm 5}{8}. \] This results in two possible solutions: 1. \( x = \frac{16}{8} = 2 \) 2. \( x = \frac{6}{8} = \frac{3}{4} \) Thus, the solutions to the equation are \[ x = 2 \quad \text{and} \quad x = \frac{3}{4}. \]